2014
DOI: 10.1371/journal.pone.0104055
|View full text |Cite
|
Sign up to set email alerts
|

Association of Liposome-Encapsulated Trivalent Antimonial with Ascorbic Acid: An Effective and Safe Strategy in the Treatment of Experimental Visceral Leishmaniasis

Abstract: Background:Visceral leishmaniasis (VL) is a chronic debilitating disease endemic in tropical and subtropical areas, caused by protozoan parasites of the genus Leishmania. Annually, it is estimated the occurrence of 0.2 to 0.4 million new cases of the disease worldwide. Considering the lack of an effective vaccine the afflicted population must rely on both, an accurate diagnosis and successful treatment to combat the disease. Here we propose to evaluate the efficacy of trivalent antimonial encapsulated in conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…From week 6, the positivity for the DNA parasite remains constant in both organs, but with the higher percentages of positivity and parasitic load in the liver compared to the spleen. These results are in accordance with those of other authors who detected parasites in all spleen and liver samples at week 6 after infection (14,17). Our results revealed that the initial commitment of the strain is to the liver, and over the course of the infection the parasite disseminates to the spleen, corroborating with the fact that the liver is the compartment of acute resolving infections, whereas the spleen is the compartment of parasite persistence (18).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…From week 6, the positivity for the DNA parasite remains constant in both organs, but with the higher percentages of positivity and parasitic load in the liver compared to the spleen. These results are in accordance with those of other authors who detected parasites in all spleen and liver samples at week 6 after infection (14,17). Our results revealed that the initial commitment of the strain is to the liver, and over the course of the infection the parasite disseminates to the spleen, corroborating with the fact that the liver is the compartment of acute resolving infections, whereas the spleen is the compartment of parasite persistence (18).…”
Section: Discussionsupporting
confidence: 93%
“…The murine model is comparable to self-controlled oligosymptomatic cases and therefore is useful for the study of the protective immune response; this model has significantly contributed to the understanding of the hypothesis of immune-mediated mechanisms relevant to understand distinct aspects of leishmaniasis, as well as identified relevant elements associated with protective response in chemotherapeutic and immunoprophylactic approaches (11,12). In addition, many studies have used the murine experimental model of VL and produced similar results of pathological, immunological, and parasitological evaluation using different strategies of treatments (immunotherapy and immunochemotherapy) (13)(14)(15)(16). Thus, our VL model corroborates with other studies using BALB/c mice as an experimental model for treatment evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we first prepared and characterized the liposomal formulations. The SbIII encapsulation efficiency in liposomes was similar to values reported in the literature (between 6.5 and 15.0%) [ 20 , 26 – 28 ]. The vesicles showed a homogeneous size distribution.…”
Section: Discussionsupporting
confidence: 87%
“…Conventional liposome (Lconv) was prepared using DSPC and CHOL (5 : 4), at 120 g/L. Liposomes were prepared using the freeze and thaw technique followed by extrusion, as described previously, with modifications [ 18 20 ]. Briefly, the lipids were solubilized in chloroform and the formation of the lipid film occurred by solvent exclusion using a rotary evaporator operating at 70 rpm at 60°C for 20 min under reduced pressure.…”
Section: Methodsmentioning
confidence: 99%
“…The encapsulation efficiency for Sb-entrapped liposomes varied from 8 to 50%, depending on the preparation method (4) . Trivalent antimony entrapped in a liposome prepared by filter extrusion showed an average encapsulation efficiency of 15% (29) . Incorporation of charged lipids into bilayers has been shown to increase the aqueous volume in liposomes (30) , which was probably due to charge repulsion separating the adjacent bilayers.…”
Section: Discussionmentioning
confidence: 99%